Studentenbriefe als Quelle zur Erforschung des mittelalterlichen Kreditwesens Die Darlehen von Bruno und Basilius Amerbach im Paris zu Beginn des 16. Jahrhunderts - Hacke, Martina (Das Mittelalter, 2022)
One of the important sources for research into student credit relationships in the Middle Ages and Early Modern Times are letters by scholars. Only a small number of them from medieval times have survived. There is a bundle from two students from the time just after the turn of the 15th century, which concerns Bruno and Basilius Amerbach, who came from Basle and studied in Paris. Their correspondence is part of that of the well-known printer Johann Amerbach († 1513). It is possible to tell from these letters how Bruno and Basilius financed their studies in Paris, namely because they took out loans from specific persons there. This practice can be traced on the basis of the letters of the scholars. Here it concerned informal loans, the granting of which had been structured around the situation-related needs of the two young people. However, the substructure was based on the commercial contacts of their father and the networking structures derived from them. They arose from persons who were in the service of Johann Amerbach but also followed their own business activities, in the course of which they had to overcome the spatial distances between Basle and Paris. Hence the loans constituted a personal link between the two young people and their parents, and the letters were the tangible medium of both the family connection and the specific practice regarding loans. Keywords Letters of Students; Loans of Students; University of Paris; Paris; Basel